Design and experimental study of an air source heat pump for drying with dual modes of single stage and cascade cycle. (25th January 2018) - Shen, Jiubing; Guo, Ting; Tian, Yafen; Xing, Ziwen
Highlights: An air source heat pump drying system was designed with dual operation modes. The operation mode changes to satisfy heating demands at different conditions. A prototype is developed and its performance is experimentally studied. The drying air temperature reaches 70 °C at the heat pump's design conditions. The comparison of COPs is done for the reference of mode-switch point decision. Abstract: The heat pump drying system is a prospect technology for material drying due to its advantages of high efficiency and energy saving. This paper presents a design of an air source heat pump with dual modes for drying. The operation mode changes between a single stage and a cascade cycle to satisfy the heating demand under different ambient temperatures. A prototype of this dual-mode heat pump is developed using R22 and R134a as refrigerants. To verify the feasibility and to investigate the characteristics of this heat pump, an experimental study is carried out. According to the results of this study, the supplying air temperatures satisfied the drying demand (70 °C) when the heat pump operated at its design condition which is an ambient temperature of 0 °C for the cascade cycle and 20 °C for the single stage. With the increase of the ambient temperature, the supplying air temperature, heating capacity and electric power all increased at both operation modes. The difference of electric power between the two modes also increased with the ambient temperature, but the difference of supplying air temperature decreased. Although the variation of compressors' pressure ratio was small within each mode, the pressure ratio of the high stage's compressor changes a lot which was about 3.8 for the single stage and 5.5 for the cascade cycle. With the same supplying air temperature, the lines of coefficient of performance (COP) at different modes crossed each other. The COP of single stage was higher after an ambient temperature of 2 °C for the developed heat pump.